Cultural Competence and Cultural Sensitivity Education in University Nursing Courses. A Scoping Review - Gradellini, Cinzia; Gómez-Cantarino, Sagrario; Dominguez-Isabel, Patricia; Molina-Gallego, Brigida; Mecugni, Daniela; Ugarte-Gurrutxaga, María Idoia (Frontiers in Psychology, 2021)
When assessing the fragility that characterizes the health of an immigrant person, a culturally competent transformation of the nurse–patient teaching-learning process is necessary. Therefore, it is considered essential to incorporate cultural competence and intercultural communication in higher nursing education. Objective To determine the content and knowledge of cultural competence and intercultural communication offered in higher education in nursing courses. Design The Campinha-Bacote model of cultural competence was used as the primary reference. Method A scoping review was conducted about studies published in the period 2003 and 2020. The research was conducted between May and October 2020. More than a hundred documents (books, chapters, articles, conference proceedings) have been consulted. Results Undergraduate nursing courses and postgraduate education move toward promoting cultural competence and sensitivity through teaching strategies. Conclusions Teaching projects that combine multiple competencies are more effective, including teacher training. A predominant element is a need for continuous and transversal projects. University nursing education must adapt culturally competent curricula.